Effects of high-intensity intermittent cross-training on maximal oxygen uptake - Xin Liu; Katsunori Tsuji; Yuzhong Xu; Motoyuki Iemitsu; Izumi Tabata (Sports Medicine and Health Science)
We investigated the effects of high-intensity intermittent cross-training (HIICT) on maximal oxygen uptake (V˙O2max). The HIICT consisted of alternating intermittent 20-s treadmill running (1st, 3rd, 5th, and 7th bouts) and 20-s bicycle exercise (2nd, 4th, and 6th bouts) with a 10-s rest period. Each intensity for running and bicycling of the HIICT corresponded to an oxygen demand of ∼160% and ∼170% of the V˙O2max, respectively. Fifteen healthy young males (aged [24 ​± ​1] yrs) were randomly assigned to training (TG, n ​= ​8) and non-training control (CG, n ​= ​7) groups. The TG completed this HIICT daily 4 days/week for 6 weeks. Significant group ​× ​time interactions were observed for both the running and bicycling V˙O2max (p ​< ​0.001 each). After the training, the V˙O2max for both running ([57.4 ​± ​4.8] mL·kg−1·min−1) and bicycling ([50.6 ​± ​3.7] mL·kg−1·min−1) in the TG were significantly higher than those for running ([50.1 ​± ​3.1] mL·kg−1·min−1) and bicycling ([43.7 ​± ​3.6] mL·kg−1·min−1) in the CG, respectively (p ​< ​0.01 each). Post-hoc tests revealed a significant increase in V˙O2max for running and bicycling in the TG after the HIICT (p ​< ​0.001 each) but no significant difference in the CG. These results demonstrated that the newly developed HIICT increases the V˙O2max for both running and bicycling.